Analysis Of The Cash Disbursement Accounting System - Sari, Maya Rizki; Dwinata, Arif; Pradila, Ifni (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2024)
This study aims to analyze the cash disbursement system at PT. ABC located in Subarak Village, Gunung Sahilan District, Kampar Regency. Cash serves as a readily available medium of exchange for financing company operations; however, its inherent characteristics—such as being untraceable in ownership and easily transferable—make it susceptible to misappropriation or embezzlement. The research employs a descriptive analysis approach, focusing on the cash disbursement accounting system at PT. ABC. Data sources include primary data obtained through interviews with relevant personnel and secondary data from company financial records. The analysis reveals that the cash receipt and disbursement system at PT. ABC is not functioning effectively. Key deficiencies identified include the absence of authorization from authorized personnel, lack of segregation of duties, and inadequate internal control systems. These shortcomings pose significant risks to the integrity of cash management and financial reporting within the organization. Furthermore, the study acknowledges limitations, such as the focus on a single company, which may restrict the generalizability of the findings to other contexts. Future research is recommended to explore cash management practices across different industries and to assess the impact of implementing robust internal control systems on the effectiveness of cash disbursement processes. This study contributes to the understanding of cash management practices and highlights the importance of establishing effective internal controls to mitigate risks associated with cash handling in organizations.